1991
DOI: 10.1128/aem.57.2.601-603.1991
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Wine Malolactic Fermentation with Nisin and Nisin-Resistant Strains of Leuconostoc oenos

Abstract: The polypeptide nisin (100 U/ml) prevented malolactic fermentation in wines by indigenous or intentionally added lactic acid bacteria. Nisin (100 U/ml)-resistant mutants of Leuconostoc oenos were obtained and used with nisin in wine to carry out a pure-culture malolactic fermentation in the presence or absence of other lactic acid bacteria. Nisin degradation by mutants was not observed, and residual nisin was detectable in wines 4 months after it was added. Results indicated that nisin or nisin with resistant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

1993
1993
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(23 citation statements)
references
References 9 publications
2
20
0
1
Order By: Relevance
“…Spontaneous nisin-resistant mutants can be selected from populations of most nisin-sensitive, Gram-positive bacteria after exposure to high concentrations of nisin. Nis"' has been reported in lactococci [117,118], Listeria [123], and Leuconostoc [123,124]. Since nisin acts upon liposomes [78] and Gram-negative bacteria [12,77], it does not appear to require a specific protein receptor in the membrane for biological activity.…”
Section: Nisin Immunity and Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Spontaneous nisin-resistant mutants can be selected from populations of most nisin-sensitive, Gram-positive bacteria after exposure to high concentrations of nisin. Nis"' has been reported in lactococci [117,118], Listeria [123], and Leuconostoc [123,124]. Since nisin acts upon liposomes [78] and Gram-negative bacteria [12,77], it does not appear to require a specific protein receptor in the membrane for biological activity.…”
Section: Nisin Immunity and Resistancementioning
confidence: 99%
“…Second, intentional selection of Nis m derivatives can be used to create specialized culture combinations for applications in food bioprocessing that rely on the addition of nisin or use of nisin-producing starter cultures. For example, Daeschel et al [124] employed Nis m derivatives of Lc. oenos to initiate secondary fermentations in wine, where nisin was added to control the growth of undesirable secondary microflora.…”
Section: Nisin Immunity and Resistancementioning
confidence: 99%
“…Like beer, wine can also suffer from spoilage as a result of undesirable LAB growth and subsequent production of detrimental compounds 40 . Sulphur dioxide is often used to suppress LAB in winemaking although its use is strictly regulated.…”
Section: Nisinmentioning
confidence: 99%
“…Previously, it was suggested that the use of nisin in wine would be limited to wines that do not undergo malo-lactate fermentation. Rccently, Daeschel was able to construct nisin-rcsistant mutants of Leuconostoc oenos that were ablc to perform a malo-lactate fermentation in wine containing 10!t IU ml ~ of nisin [32].…”
Section: Nisin Application In Fermented Beveragesmentioning
confidence: 99%